RTHP-21. CHARACTERIZATION OF RADIATION THERAPY EFFECTS ON CEREBRAL VASCULATURE IN PEDIATRIC BRAIN TUMOR SURVIVORS. (5th November 2018) - Avadiappan, Sivakami; Morrison, Melanie; Jakary, Angela; Felton, Erin; Mueller, Sabine; Lupo, Janine
Abstract: Although cranial Radiation Therapy (RT) plays an important role in the treatment of pediatric brain tumors, it is often associated with significant long-term side effects such as cognitive decline and vascular injury in the form of cerebral microbleeds (CMBs). Understanding the evolution of CMBs and the effect of their presence on surrounding vascular integrity could serve as a risk factor for evaluating the severity of radiation related injury in these children. The goal of this study was to explore the effects of RT on arterial structure, including how arterial thickness changes based on proximity to CMBs of varying sizes. 17 patients (ages 10–24) treated with whole-brain or whole-ventricular RT for pediatric brain tumors 2 months to 16 years prior to imaging, and 3 non-irradiated control patients (ages 14–26) were scanned on a 7 Tesla MRI scanner using a novel simultaneous MRA-SWI acquisition that enables visualization of arteries, veins, and CMBs all on one image. Arterial radii were quantified from segmented vessels and the resulting distribution of vessel radii thickness was correlated with clinical information and CMB burden. Individual CMB size was related to the distance from the nearest vessel. Overall, normalized arterial volume decreased as a function of time since RT. The fraction of small arteries increased with time since RT up to 2 years, after which a decreasing trend was observed. All CMBs were located closer to veins than arteries. Although larger CMBs were initially farther away from the nearest vein, over time CMBs far from surrounding vasculature varied in size. These results suggest that after a CMB forms, the surrounding vasculature narrows and eventually recedes. Current work is investigating the spatial distribution of these findings throughout the brain and how they relate to measured cognitive deficits in these children.